2015
DOI: 10.1128/jvi.00214-15
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus 1 US3 Phosphorylates Cellular KIF3A To Downregulate CD1d Expression

Abstract: Herpes simplex virus 1 (HSV-1) causes one of the most prevalent herpesviral infections in humans and is the leading etiological agent of viral encephalitis and eye infections. Our understanding of how HSV-1 interacts with the host at the cellular and organismal levels is still limited. We and others previously reported that, upon infection, HSV-1 rapidly and efficiently downregulates CD1d cell surface expression and suppresses the function of NKT cells, a group of innate T cells with critical immunoregulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…A recent publication indicates that KIF3A, a subunit of kinesin-2 motor protein that transports protein complexes along microtubule tracks, is required for CD1d surface expression (43). KIF3A can be phosphorylated by the viral kinase U S 3 and downregulates CD1d surface expression (43). This is consistent with our discovery that VP22, a viral protein modifies host cell microtubule network, is important in inhibiting CD1d-mediated antigen presentation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A recent publication indicates that KIF3A, a subunit of kinesin-2 motor protein that transports protein complexes along microtubule tracks, is required for CD1d surface expression (43). KIF3A can be phosphorylated by the viral kinase U S 3 and downregulates CD1d surface expression (43). This is consistent with our discovery that VP22, a viral protein modifies host cell microtubule network, is important in inhibiting CD1d-mediated antigen presentation.…”
Section: Discussionsupporting
confidence: 79%
“…Nonetheless, gB itself is not sufficient to inhibit CD1d-mediated antigen presentation (35). A recent publication indicates that KIF3A, a subunit of kinesin-2 motor protein that transports protein complexes along microtubule tracks, is required for CD1d surface expression (43). KIF3A can be phosphorylated by the viral kinase U S 3 and downregulates CD1d surface expression (43).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HSV-1 Us3, the best-studied alphaherpesvirus Us3 homologue, blocked apoptosis (16)(17)(18)(19), promoted vesicle-mediated nucleocytoplasmic transport of nucleocapsids through nuclear membranes (20)(21)(22)(23), promoted gene expression by blocking histone deacetylation (24)(25)(26), controlled infected-cell morphology (15,18,27), modulated host immune systems (28)(29)(30)(31)(32)(33)(34)(35), stimulated mRNA translation by activating mTORC1 (36), regulated intracellular trafficking of the abundant virion component UL47 (37) and the essential envelope glycopro-tein B (gB) (38,39), and upregulated the enzymatic activity of viral dUTPase (vdUTPase) (40). These observations suggested that HSV-1 Us3 is a multifunctional protein that regulates various cellular and viral functions by phosphorylating a number of cellular and viral protein substrates.…”
mentioning
confidence: 99%
“…Thus, by interfering with complement components HSVs increase their viability in the mucosae and sera of infected patients, which favors the infection of target cells. [175][176][177] gC, gD (glycoprotein C, D); U S 3 (short unique region 3); C3b, C5 (complement component 3b, 5); NK (natural killer cell); CD112 (nectin-2); DNAM-1 (DNAX accessory molecule-1); MICA (MHC class I polypeptide-related sequence A); ULBP1, 2, and 3 (UL16 binding protein 1, 2 and 3); KIF3A (kinesin family member 3); CD1d (antigen-presenting glycoprotein CD1d).…”
Section: Interference With Complement Functionmentioning
confidence: 99%